Wheat seeds exposed to heat during formation can germinate at high temperatures - Toda-Matsunaga, Sachiko; Toda, Yusuke; Mega, Ryosuke; Tadano, Shota; Alyza, Megumi; Yamasaki, Yuji; Akashi, Kinya; Tsujimoto, Hisashi (Frontiers in Plant Science, 2025)
A capacity for reliable germination under elevated temperatures is a crucial factor in maintaining the stability of bread wheat (Triticum aestivum) yields in the context of climate change. Although the environment of the parent plant during growth is a known factor affecting seed germinability, the effect of this environment on the heat tolerance of wheat seeds has not been investigated in detail. To investigate the effect of exposure to high temperatures during growth, plants were exposed to 38°C at various growth stages. In germination test, seeds exposed to heat during their development had better heat germinability than the control. On the other hand, high temperatures before the seed development stage resulted in a lower temperature germinability compared to the control. To identify critical factors that altered heat germinability, we analyzed heat shock protein expression, fatty acid composition, and metabolite profiles. High-temperature treatment during seed formation increased the expression of heat shock proteins and reduced the degree of unsaturation of fatty acids in the seeds, which may enhance the ability of seeds to survive and germinate at high temperatures. There was a significant treatment effect on the overall metabolite content of the seeds. PLS regression analysis using the germination test results revealed that taurine, thymidine, beta-alanine, sinapic acid, and deoxyguanosine contributed significantly to germination rate. These findings suggest that the combined influence of these metabolites may play a role in acquiring seed germinability under high-temperature conditions during the growth period of the parent plants. These findings suggest potential components of a molecular mechanism in bread wheat that is triggered by high temperature during seed development and results in the acquisition of heat germinability.